The ThSOS3 Gene Improves the Salt Tolerance of Transgenic Tamarix hispida and Arabidopsis thaliana - Liu, Zhongyuan; Xie, Qingjun; Tang, Feifei; Wu, Jing; Dong, Wenfang; Wang, Chao; Gao, Caiqiu (Frontiers in Plant Science, 2021)
The salt overly sensitive (SOS) signal transduction pathway is one of the most highly studied salt tolerance pathways in plants. However, the molecular mechanism of the salt stress response in Tamarix hispida has remained largely unclear. In this study, five SOS genes (ThSOS1–ThSOS5) from T. hispida were cloned and characterized. The expression levels of most ThSOS genes significantly changed after NaCl, PEG6000, and abscisic acid (ABA) treatment in at least one organ. Notably, the expression of ThSOS3 was significantly downregulated after 6 h under salt stress. To further analyze ThSOS3 function, ThSOS3 overexpression and RNAi-mediated silencing were performed using a transient transformation system. Compared with controls, ThSOS3-overexpressing transgenic T. hispida plants exhibited greater reactive oxygen species (ROS)-scavenging capability and antioxidant enzyme activity, lower malondialdehyde (MDA) and H2O2 levels, and lower electrolyte leakage rates under salt stress. Similar results were obtained for physiological parameters in transgenic Arabidopsis, including H2O2 and MDA accumulation, superoxide dismutase (SOD) and peroxidase (POD) activity, and electrolyte leakage. In addition, transgenic Arabidopsis plants overexpressing ThSOS3 displayed increased root growth and fresh weight gain under salt stress. Together, these data suggest that overexpression of ThSOS3 confers salt stress tolerance on plants by enhancing antioxidant enzyme activity, improving ROS-scavenging capability, and decreasing the MDA content and lipid peroxidation of cell membranes. These results suggest that ThSOS3 might play an important physiological role in salt tolerance in transgenic T. hispida plants. This study provides a foundation for further elucidation of salt tolerance mechanisms involving ThSOSs in T. hispida.